Pengaruh Model Project Based Learning (PjBL) dalam Proyek Pengolahan Limbah Organik Terhadap Literasi Sains Siswa - Sulastri Sulastri; Deassy Siska; Widya Widya; Muliani Muliani; Tulus Setiawan (Universitas Hamzanwadi, 2025)
Thle Effelct olf thle Projelct Balsed Lelarning (PjlBL) Modell iln Orgalnic Walste Procelssing Projelcts oln Stuldents' Scilentific Lilteracy. Thlis relsearch ils a qulantitative stuldy wilth a qulasi-expelrimental relsearch delsign iln thle forlm olf a Nonelquivalent Conltrol Groulp Delsign. Thle popullation olf thlis studly conlsisted olf 107 elighth-gralde stuldents alt SMlP N 1 Nilsam. Thle samlpling teclhnique useld wals pulrposive salmpling, wilth a totlal olf 32 stuldents iln elach cllass. Clalss VIII-A selrved als thle exlperimental cllass, imlplementing thle PjlBL modlel iln thle orgalnic walste procelssing projelct. Thle telchniques anld inlstruments folr dalta collelction iln thlis studly inlcluded writteln telsts, obselrvations, anld intlerviews. Thle collelcted dalta welre anlalyzed ulsing delscriptive anlalysis thlrough dalta collelction, dalta orgalnization, anld conlclusion dralwing. stuldy shlow thalt thle averlage prletest scorle obtalined by stuldents iln thle exlperimental cllass wals 54.21, whille thle avelrage postltest scorle wals 84.21, wilth aln N-Galin Scorle of 0.67, caltegorized als moderalte. Iln conltrast, thle averalge pretlest scorle iln thle conltrol clalss wals 57.65, alnd thle avelrage postltest scorle wals 68.43, wilth aln N-Galin Scorle olf 0.26, caltegorized als lolw. Thle higlher inlcrease iln stuldents' scielntific litelracy achielvement iln thle elxperimental clalss inldicates thlat thle imlplementation olf thle PjlBL modell iln tlhe orgalnic walste procelssing projelct hals aln imlpact oln stuldents' scielntific litelracy. Thlis finlding ils relinforced by tlhe relsults olf staltistical anlalysis usling aln inldependent salmple telst iln SPlSS Velrsion 27, whilch shlowed a silg (2-taliled) vallue olf 0.000 < 0.05, melaning thlat H₀ wals reljected alnd H₁ wals alccepted. Thlus, ilt caln ble conlcluded thalt thle PjlBL modell iln thle orgalnic walste procelssing projelct silgnificantly affelcts stuldents' scielntific lilteracy.